2013
DOI: 10.1002/phar.1364
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Views on Pharmacogenomic Testing

Abstract: Pharmacogenomics has an important role in the evolution of personalized medicine, and its widespread uptake may ultimately depend on the interests and perspectives of key players in health care. Our aim was to summarize studies on stakeholder perspectives and attitudes toward pharmacogenomic testing. Thus, we conducted a review of original research studies that reported stakeholder views on pharmacogenomic testing using a structured approach in PubMed, International Pharmaceutical Abstracts, Cumulative Index t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 44 publications
(153 reference statements)
0
34
0
Order By: Relevance
“…According to another study, physicians found utility in providing PGx testing to improve patient outcomes by individualizing treatment to guide medication decisions and to decrease time and cost for maximizing the benefits of needed medications [35]. Utilizing PGx testing in order to avoid side effects from medication and improve medication effectiveness have been proposed as benefits in other studies as well [5,17,20,[35][36][37].…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 99%
“…According to another study, physicians found utility in providing PGx testing to improve patient outcomes by individualizing treatment to guide medication decisions and to decrease time and cost for maximizing the benefits of needed medications [35]. Utilizing PGx testing in order to avoid side effects from medication and improve medication effectiveness have been proposed as benefits in other studies as well [5,17,20,[35][36][37].…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 99%
“…Several studies have demonstrated that clinicians feel unprepared to deal with pharmacogenomics information for their patients, and are unsure about the impact that such information will have on their clinical practices. (711) Thus, one of the largest barriers has been the education of providers about pharmacogenomics, both generally, and at the time of drug prescribing using clinical decision support (CDS) tools.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggest high patient interest in PGx testing [8][9][10][11][12], particularly to improve drug outcomes and predict the risk of serious adverse events, with lower interest in testing for mild adverse events [9]. In addition to the perceived benefits of PGx testing, several concerns have been raised including cost of the test and insurance coverage, the predictive value of the test, testing turnaround time, privacy, affordability of recommended drug based on the test result and patient sovereignty [7,[13][14][15][16][17]. The limitations of PGx testing to definitively determine which side-effects patients may experience has also been perceived as a weakness of testing [9,10].…”
mentioning
confidence: 99%